If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 6y + 12 Reorder the terms: 2y = 12 + 6y Solving 2y = 12 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 2y + -6y = 12 + 6y + -6y Combine like terms: 2y + -6y = -4y -4y = 12 + 6y + -6y Combine like terms: 6y + -6y = 0 -4y = 12 + 0 -4y = 12 Divide each side by '-4'. y = -3 Simplifying y = -3
| 11p+-4p+-18p+-p-11p=-13p | | -.25x+6=.6666666666667x+28 | | 27=-12+7x-3x | | 5(7x+4)=195 | | 5(x+5)+9=9x-4(x-6) | | 2(3a+4b)+7b+3a= | | 9x-165+x=85 | | 5x+7y=560 | | (2)(-7)-(3)(-4)= | | 18g+3g-7g+4g-17g=16 | | 180363428x=180007263627 | | 2x-5(3/2)=5 | | 7(2z+1)=36 | | .5(14x+30)=12x+55 | | 55=45-u | | 15x^2=2x+4 | | 2x+x+8=41 | | 14u-10u+2u-5u=9 | | 18H-12h-h-2h+2h=10 | | x+0.25=2.50 | | 6=-16t^2+15t+100 | | 2(-7x+9)=130 | | 2p+3=6 | | 3x-5x+9x^2-5=0 | | -11+3x=2x+29 | | 4a=89 | | -19-16n=11-13n+12 | | x+x+x+2x+2x=21 | | -4x-5x=9-7 | | 2x^2+5=-15 | | -203+3x=67-6x | | (x-5)(x-12)=44 |